Does occupational exposure to brown coal dust cause a decline in lung function?. Issue 9 (September 1997) - Finocchiaro, C; Lark, A; Keating, M; Ugoni, A; Abramson, M
Abstract : OBJECTIVES: To determine if the rate of change in forced expiratory volume in one second (FEV1) in subjects with high exposure to Latrobe Valley brown coal dust was significantly greater than the rate of change among subjects with low exposure. METHODS: A retrospective dynamic cohort design with variable time windows. This study was conducted over a period of 14 years from 1980 to 1994 and used data collected by the State Electricity Commission (SEC) Lung Function Unit for an asbestos surveillance programme. The subjects were exposed to low, medium, or high levels of coal dust. Basic spirometry with wedge bellows spirometers was used to assess lung function. A general linear model (GLM) was used to assess the effects of smoking and exposure to coal dust upon the change in forced expiratory volume in one second (FEV1) while adjusting for age and height. RESULTS: The mean (95% confidence interval (95% CI) rate of decline in FEV1 was 40 (36 to 44) ml/year. Age was a significant predictor of change. A significant effect was found for smoking (P = 0.02) and for exposure to coal dust (P = 0.008). The only significant difference with exposure to coal dust was between the high and mixed exposure categories. CONCLUSION: There is no convincing evidence of excessive decline in FEV1 with exposure to coal dust > 0.75 mg/m3. The absence of a dose response relation provides some evidence against a causal relation. On the basis of this study, reduction of the exposure standards currently applied to brown coal dust in the Victorian electricity industry is not warranted to prevent respiratory disease.